Processos interativos entre professora ouvinte e estudantes visuais em aula de língua inglesa: primeiras aprendizagens (Revista Diálogos, 2017)
RESUMO: Este trabalho visa apresentar as primeiras impressões de uma estudante de graduação que atuou como professora de inglês no Projeto Piloto “Ensino de Inglês para o Acadêmico Surdo”. Por ser uma turma de acadêmicos ouvintes e visuais3, destacam-se no relato da estudante/professora os processos interativos entre os participantes durante as aulas. Esse Projeto insere o estudante de graduação e futuro professor em experiências de ensinar que são para ele, também, momentos de aprendizagem. Este estudo pretende contribuir para formação de professores de inglês para estudantes visuais. PALAVRAS-CHAVE: Ensino de inglês. Formação de professores. Sujeito visual. ABSTRACT: This article focuses on an English as a Foreign Language Course that was offered by an undergratuate hearing teacher for undergraduate deaf and hard of hearing students, all of them Brazilian, in a Pilot Project for student teaching practice in a Brazilian university. This study discusses the teacher ́s point of view regarding the interactions that took place in the classroom, and points out how the teacher managed language use considering the use of Brazilian Sign Language (Libras), Portuguese and English during the class. We found that in the teacher ́s opinion, visual materials and resources in English are essencial for the teaching of an oral language in its written modality and that the use of Libras by the hearing teacher enhances deaf students ́motivation to interact with one another in the class and promotes language learning. KEY-WORDS: English. Brazilian deaf sudents.Teacher formation.